Learning and Challenges of Social Action: Systematization of the Experience of the School of Psychology, University of Costa Rica - Maroto-Vargas, Adriana (2021)
Social Action, a Latin America Public University pillar, has been developed from different models. As this theoretical and historical framework is taken as a reference, the article presents a critical systematization of the Social Action experience of the School of Psychology at the University of Costa Rica during the period 2000-2015. The research considered the systematization of experiences as a methodological approach from which a critical interpretation of the analyzed process was made. Documentary sources were consulted, and 14 interviews were conducted; these techniques allowed the construction of a timeline. Subsequently, a workshop was held, and it identified the 14 discussion axes analyzed in this article; they include political, academic, and ethical aspects of Social Action. It is concluded that Social Action had an improvement since it was defined as a priority, and a political position guiding the work was established. The main identified challenges were the dissemination, the definition of project closure criteria, the systematization and evaluation, as well as the construction of a project articulation strategy with each other and with other substantive activities of the university (teaching and research).